Pemanfaatan ‘Gunung Batu’ Sebagai Sumber Belajar IPS (Studi Deskriptif Kualitatif di ‘Gunung Batu’ Lembang Kabupaten Bandung Barat) - Alamsyah, Wildan; Abdulkarim, Aim; Mulyadi, Asep (Peneliti.net, 2024)
A good understanding that the teacher is not the only source of learning will have an impact on students. So far, social studies learning is known to be done by conventional learning methods, namely by the lecture method, while there are many environments around students that can be used as learning resources in social studies learning. This study aims to describe the utilization of ‘Gunung Batu’ Lembang that can be used as a learning resource in social studies learning. This research uses a qualitative approach with descriptive methods by directly observing 'Gunung Batu' Lembang, conducting interviews with the manager, one of the social studies teachers, and students of SMP Negeri 2 Lembang, as well as documentation. The results showed that ‘Gunung Batu’ Lembang can be utilized as a social studies learning resource. The values found include cultural values, science values, educational values, tourism values, and economic values. These values can then be correlated with existing social studies learning materials in grades 7-9. The utilization of ‘Gunung Batu’ as a social studies learning resource was last implemented in KTSP due to various obstacles encountered both internal and external factors.